The effectiveness of practicum-based worksheet based on salt hydrolysis material viewed from the aspect of laboratory skills and interpersonal intelligence learners - Elsa Ari Astuti; Sri Wardani; Sri Kadarwati; Kasmui Kasmui (Intelektual Pustaka Media Utama, 2019)
This study aims to determine the effectiveness of a practicum worksheet (LKPPD) based on guided inquiry and the response of learners as users. The effectiveness of LKPPD is seen from aspects of laboratory skills and students' interpersonal intelligence on hydrolysis material. This type of research is qualitative and quantitative. Data collected by interview, observation, and questionnaire. The results showed that LKPPD that has been developed is effective because 76% of students have laboratory skills with very high category and 96.5% of students have interpersonal intelligence with a minimum category high. In addition, this LKPPD received a positive response from learners as users with a percentage score of 77.9%.